Pengaruh Modal Kerja Terhadap Profitabilitas Pada Perusahaan Rokok Yang Terdaftar di Bursa Efek Indonesia Tahun 2017 -2021 - Ni Putu Faradha Azhari; Antonius Pilippus Kurniawan; Elisabet Luju (Jurnal Projemen UNIPA, 2022)
The problem in this study is the fluctuating working capital in cigarette companies listed on the Indonesia Stock Exchange in 2017-2021. This study aimed at determining the influence of working capital on profitability. The population in this study was all cigarette companies listed on the Indonesia Stock Exchange totaling 5 companies. Research samples were obtained using the purposive sampling method. The samples used were from 4 companies. Data was collected through documentation and analyzed using descriptive statistical methods and inferential statistics, namely simple linear regression. Hypothesis testing was done through a t-test. The results of the descriptive analysis revealed that: (1) Working capital had an average value (mean) of IDR.14,277,908,600 of the total working capital. (2) Gross profit margin had an average value (mean) of 19.8 which shows that every IDR. 1 sale can be fulfilled with IDR.19.8 gross profit owned by the company. The results of the t-test statistic indicated that working capital (X) had a positive and significant influence on the variable gross profit margin (Y). The results of the determination analysis (R²) showed that the working capital variable was able to explain the fluctuation of profitability of cigarette companies listed on the Indonesia Stock Exchange by 21.4%.